The Degree of Using Social Media in Distance Learning in the First Basic Stage's Students from the Perspectives of Their Teachers during Corona Pandemic - Majdoleen Hamdi Mahmoud Mansour; Ashraf Ali Bani Yassin (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aimed to reveal the degree of use of social media in distance learning for students in the first basic stage from the point of view of their teachers during the Corona pandemic. The sample of the study consisted of (231) male and female teachers of the basic stage in the Zarqa Governorate during the academic year (2022/2021). The results of the study showed that the degree of using social media in distance learning for students in the first basic stage was low, and the results also showed that there were no statistically significant differences at (α≤ 0.05) toward the degree of using social media in distance learning according to the variable Gender, experience, and educational qualification. The study recommended holding training courses to qualify teachers to use E-learning skills and social media in student learning, especially for the basic stage.